Localization Watermarking for Authentication of Text Images in Quran - Syifak Izhar, Hisham; Jasni, Mohamad Zain; Afifah Nailah, Muhamad; Gran, Badshah (IEEE, 2013)
The phenomenon of widespread usage of smart phone has encouraged many android applications to be produced, by free or paid. Nowadays, with the trend of communicating through social networking applications and social networking sites, Muslims tend to share the image of verse from the Quran to the sites. Several concerns regarding security and copy control of the verse text image have aroused, and among the solution to this issue is watermarking. This paper has conducted a research proposing an authentication watermark with spiral manner which show a good numbering system of embedding. Subsequently, it proposed a localization and restoration watermarking scheme to be applied in the Quran application as a function before sharing.